2017
DOI: 10.1080/2162402x.2016.1278332
|View full text |Cite
|
Sign up to set email alerts
|

Calreticulin promotes immunity and type I interferon-dependent survival in mice with acute myeloid leukemia

Abstract: Exposure of cancer cells to particular chemotherapeutic agents or γ-irradiation induces a form of cell death that stimulates an immune response in mice. This “immunogenic cell death” requires calreticulin (CRT) translocation to the plasma membrane, which has been shown to promote cancer cell phagocytosis. However, it remains unclear whether the effect of CRT on cancer cell phagocytosis is alone sufficient to affect tumor immunity. Acute myeloid leukemia (AML) cells expressing cell-surface CRT were generated in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 25 publications
0
36
0
Order By: Relevance
“…Our previous studies demonstrated the down‐regulation of CRT during DADS‐induced differentiation in HL‐60 cells and indicated that CRT was involved in cell proliferation, invasion, and differentiation in DADS‐treated HL‐60 cells . Numerous studies have demonstrated that CRT could play an essential role in AML cell proliferation and invasion, and therefore may be an important target for AML .…”
Section: Discussionmentioning
confidence: 99%
“…Our previous studies demonstrated the down‐regulation of CRT during DADS‐induced differentiation in HL‐60 cells and indicated that CRT was involved in cell proliferation, invasion, and differentiation in DADS‐treated HL‐60 cells . Numerous studies have demonstrated that CRT could play an essential role in AML cell proliferation and invasion, and therefore may be an important target for AML .…”
Section: Discussionmentioning
confidence: 99%
“…7 Moreover, stable transfection of cells with a CALR variant that is tethered to the surface of the plasma membrane is sufficient to preclude the growth of cancers in vivo. 7,65 To Figure 4B). Thus, the difference between parental vs hyperploid cells cultured in vitro in the expression of individual genes (black points in Figure 4C) is far more important than that between hyperploid cells passaged through ID vs IC mice (red points in Figure 4C).…”
Section: Immunosurveillance Against Hyperploid Cancer Cells-impact mentioning
confidence: 97%
“…Indeed, depletion of ERp57, which is required for CALR exposure, abolishes the immunoselection in favor of a reduced ploidy . Moreover, stable transfection of cells with a CALR variant that is tethered to the surface of the plasma membrane is sufficient to preclude the growth of cancers in vivo …”
Section: Introductionmentioning
confidence: 99%
“…While soluble DAMPs generally deliver chemotactic and immunostimulatory signals, CALR exposed on the membrane of dying cells and dead cell corpses supports their uptake by APCs in the context of type I IFN production. 4,5 Consistent with this notion, elevated levels of CALR on surface of malignant blasts has been linked with improved prognosis in patients with acute myeloid leukemia (AML), 6,7 correlating with superior T-cell dependent immunity. 6 As the contribution of lymphoid cells other than T cells to anticancer immunity driven by membrane-exposed CALR was unclear, we set to investigate the potential involvement of natural killer (NK) cells, which are gaining considerable momentum as actionable items for cancer immunotherapy.…”
mentioning
confidence: 87%